Diagnosis of the perspective condition of the investment activity of the cargo auto-operating enterprises - Malakhova, Yuliia (Technology audit and production reserves, 2018)
The object of research is the investment activity of cargo auto-operating enterprises. Investment activity is a generalizing characteristic of the state of investment activity, which is determined by its size and efficiency within the existing financial potential of an economic entity. Indicators of the state and efficiency of investment activity characterize the current state of investment activity, and financial potential – its prospective state. Therefore, a system of private indicators was used to diagnose the prospective state of the investment activity of cargo auto-operating enterprises, covering an assessment of the financial possibilities for raising its level. This system covers the assessment of own and attracted sources of financing investment expenses. In particular, to assess the direction of using own sources of financing investment activities, an algorithm for estimating the targeted use of hoarding profits and depreciation deductions are used. The results of the evaluation of the possibilities of increasing the investment activity of the enterprise show their considerable limitations. An assessment of the use of own sources of financing shows that, on average, only 30 % of profitable cargo auto-exploitation enterprises of the hoarding profit and depreciation charges are used for their intended purpose. At the same time, 24 % of the enterprises studied internal sources of financing investment expenditures are fully used for no purpose – to meet the additional requirements of operating activities. A low level of attraction of borrowed sources of financing is noted – only 20 % of the entire set of enterprises used loan funds. This is due to low values of current liquidity ratio and operating profitability of assets. The value of the first indicator, although it indicates the provision of loans with current assets, however, remains below the standard. The level of operational profitability does not exceed the interest on bank loans, which makes it impossible to pay them. Consequently, the assessment of the future state of investment activity of cargo auto-operating enterprises indicates the limitations of their own and attracted sources of financing investment expenditures, hinders the economic development of these economic entities. This requires a review of their investment strategy.